Serum decorin measurement in prediction of the risk for preterm birth - Mehmet Aral Atalay; Turan Ozmen; Bilge Cetinkaya Demir; Isil Kasapoglu; Guven Ozkaya (Elsevier, 2018)
Objective: To define serum decorin (sDEC) levels in healthy pregnants and in patients with preterm labor (PTL), and to introduce possible role of sDEC in predicting the risk for preterm birth (PTB). Materials and methods: Thirty-one women with diagnosis of PTL between 24th to 32nd weeks of pregnancy were compared with 44 healthy pregnants in this prospective case-control study. Maternal blood sDEC and uterine cervical length (CL) measurements were conducted at referral. Results: Median sDEC level was significantly decreased in PTL group (p = 0.013). Median CL was significantly shorter in PTL group (p < 0.001). There was not any correlation between sDEC level and maternal age, BMI, and gestational age at blood sampling time within PTL (p = 0.955, p = 0.609, p = 0.079, respectively) and control groups (p = 0.652, p = 0.131, and p = 0.921, respectively). There was not any association between sDEC level and PTB within 7 days, before 34th weeks, but before 37th weeks there was (p = 0.206, 0.091, and p = 0.026, respectively). There was not any correlation between sDEC level and the CL in PTL group (p = 0.056). Conclusions: sDEC has a limited effect in prediction of PTB within a week or before 34th weeks. Combination of sDEC with CL measurements predicted PTB before 37th weeks.conclusion